THE EFFECT OF IRANIAN FEMALE EFL LEARNERS’ POLITENESS STRATEGIES AWARENESS ON THEIR LETTER WRITING ABILITY - Faezeh Yousefian Dastmalchi (University of Kuningan, 2014)
Abstract: This research examines the effect of teaching politeness strategies based on the models proposed by Brown and Levinson (1987) and Leech (1983) to intermediate English learners on their ability in writing more polite letters. The instrumentation includes an IELTS test, used as a placement test, an inventory, used to measure learners’ awareness of politeness strategies, and a letter-writing test, used as a measurement of learners’ ability in using politeness strategies. Among all the participants, twenty of them were put in the control group, and twenty-four of them in the experimental group, who went under the treatment. They were taught how to write politely based on the politeness strategy models proposed by Brown and Levinson (1987) and Leech (1983). After the treatment, learners wrote letters to the same people with the same situations. Comparing the twenty learners in the control group with the twenty-four learners in experimental group, the researchers concluded that the treatment had a significant effect on the learners’ ability in writing more polite letters. They selected to use more formal strategies with those who they saw further distance with, and more informal strategies with more intimate people. Furthermore, the answers the learners provided to the questions of the inventory offered more awareness of politeness strategies. This implies that they were more aware of various choices of polite language that were available for them to use in the given situations.Keywords: politeness strategy, face, face threatening act